Un point de vue actuariel sur le SIDA - A. Ross, Jacques (Assurances, 1988)
After the two world wars, AIDS is without a doubt the worst calamity of modern times and the number one problem of this decade. It is quite surprising that Nostradamus did not predict that a phenomenon such as AIDS would be among the cataclysms of the modern area. Perhaps he thought that medical science would at this point be so advanced that such a disease could be conquered without us insurers losing our shirts. In actual fact, AIDS is a very serious problem which must be addressed before it is too late.